Bare bones - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2003)
It's a summer of record-breaking heat in Charlotte, North Carolina and Dr Temperance Brennan is looking forward to her first vacation in years. She's almost out the door when the bones start appearing. First there's the newborn skeleton found in a wood stove. Who put the baby there? The mother, hardly more than a child herself, has disappeared. Next, a small plane flies into a rock face on a sunny afternoon. Both pilot and passenger are burned beyond recognition, their bodies covered with a strange black substance. What could it be? What sinister mission might the two have been on? Most puzzling is a cache of bones unearthed in a remote corner of the county. Some animal, some human, the bones are enough to keep Tempe busy for a long time. All the pieces of the mystery seem to lead back to an isolated farm. But what happened there and who will be the next victim? Tempe must find the answers by teasing secrets from the bones - if only she can decipher them in time...